The oldest accurate record of Scenopinidae in the Lowermost Eocene amber of France (Diptera: Brachycera) - Garrouste, Romain; Azar, Dany; Nel, Andre (Zootaxa, 2016)
Eocenotrichia magnifica gen. et sp. nov. (Diptera: Scenopinidae: Metatrichini) is described and illustrated from the Lowermost Eocene amber of Oise (France) and represents the oldest definitive window fly fossil. The present discovery in the Earliest Eocene supports the Late Cretaceous—Paleocene age currently proposed for the emergence of Metatrichini.